Psychological Responses and Coping Strategies among Medical Students during Lockdown for The COVID-19 Pandemic in Malaysia - Ting, Chuong Hock; Lai, Mee Huong; Tew, Aik Kai; Chin, Joel Petrus; Lim, Jia Yi; Rubeni, Siva; Tamendaren, Salvem; Denver, Nichol (2021)
ntroduction:Coronavirus disease 2019 (COVID-19) was promulgated as a pandemic by the World Health Organi-zation (WHO). In Malaysia, the Movement Control Order (MCO) has been implemented since March coherent with the Centers for Disease Control and Prevention (CDC) recommendation. This social distancing measure induced fears and caused significant disruptions to our everyday activities, including medical students. Objective(s): We aim to examine the psychological responses of medical students of Universiti Malaysia Sarawak (UNIMAS) during the MCO and their coping strategies. Methodology: We conducted a cross-sectional study involving 245 medical students in Universiti Malaysia Sarawak. A self-administered online-based questionnaire comprised of sociodemo-graphics, mental status, and coping strategy was used. The mental status and coping skills were assessed using the Depression, Anxiety, and Stress Scale (DASS-21) and Brief COPE questionnaire respectively. IBM SPSS version 22 was used for the data analysis. Results: The prevalence of depression, anxiety, and stress were 29.8%, 27.3%. and 34.7% respectively. The most commonly used coping strategy was religion (M= 5.62, SD = 2.10) while the least practiced strategy was substance abuse (M = 2.16, SD = .77). In general, the medical students favored approach coping strategies (M = 29.19, SD = 9.27). Pre-clinical students were inclined to use avoidant coping strategies. When comparing coping strategies among both genders, male students coped more significantly with humor, while females students coped more significantly with religion. Medical students who practised approach coping strategies were less likely to develop depression. Conclusion(s): Understanding of coping strategy of the university students helps the authority to strategize psychological interventions during the present pandemic and future disaster.